Iranian Oncologists’ Attitude towards Fertility Preservation in a Sample Group - B Ghorbani; P Madahi; E Shirazi; H Sadri-Ardekani; K Kamali (JRI, 2011)
Background: Recent advances in cancer treatment have resulted in an increased number of cancer survivors. Fertility might be impaired by cancer itself or through gonadal damage as a consequence of radio-chemotherapy. Damages to reproductive organs are seen in minimally upto 30% of cancer patients. The aim of the present study was evaluate the attitude of Iranian oncologists toward fertility preservation. Methods: Thirty oncologists filled an author-designed questionnaire which included five multiple choice questions at Mahak hospital, Tehran in 2009. The data were collected and analyzed by SPSS 11.5 software. Results: More than half of the oncologists believed that radio-chemotherapy has destructive effects on reproductive organs. This study showed that as high as 67% of the respondants believed fertility preservation should be offered to all patients at risk, but 40% of them insisted that the patients should bring up the topic themselves. Only 46% of the oncologist knew about fertility preservation techniques. The greatest barriers for accepting fertility preservation by the parents of children undergoing cancer treatment were: lack of information (41%), hopelessness from treatment prognosis (33%), fear of delay in starting the treatment (15%) and the priority of child survival (11%). Conclusion: The specific challenges of counseling are time pressure between diagnosis and start of treatment, little knowledge about fertility preservation both by treating oncologists and parents; therefore a team consisting of oncologists, infertility specialists and social workers is recommended in these settings.
Keywords: Attitude, Cancer, Fertility preservation, Oncologist, Radio-chemotherapy